Expenditure Rules Related to Government Budget (under the Public Finance Act 2009) - Małgorzata Cilak (Prawo Budżetowe Państwa i Samorządu)
The article is devoted to expenditure rules related to government budget, specified in Public Finance Act. The object of analysis is the legal con-struction and functioning of expenditure rules. The article tries to respond on a question of effectiveness of these restrictions of conduct of budgetary policy. The analysis covers the rules in articles 112a–112d and 86 of Public Finance Act.